2009
DOI: 10.1021/la9015367
|View full text |Cite
|
Sign up to set email alerts
|

New Route for the Preparation of Pd and PdAu Nanoparticles Using Photoexcited Ti-Containing Zeolite as an Efficient Support Material and Investigation of Their Catalytic Properties

Abstract: A simple and unique route to synthesize nanosize Pd particles using a zeolite support including a single-site Ti oxide moiety (TS-1) under UV-light irradiation has been developed. By the photoassisted deposition (PAD) method, a Pd precursor can be deposited directly on the photoexcited tetrahedrally coordinated Ti oxide moiety within the zeolite frameworks from an aqueous solution of Pd. The subsequent reduction with H2 generates the nanosized Pd metal particles with a narrow size distribution (PAD-Pd/TS-1). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 42 publications
0
38
0
Order By: Relevance
“…45-47 One of the most studied composites is Au/TiO2 material, which can be obtained by deposition-precipitation, colloidal synthesis or photodeposition of Au. [48][49][50][51][52] Recently, the reduction of CO2 to formate has been studied using Au and Pt loaded MOFs. 53 Herein, the goal of this study is to combine the GNPmodification of TiO2 with the possible advantages of using a Tibased MOF as sacrificial precursor for the TiO2 component while also acting as support matrix for the dispersion and stabilization of small GNPs.…”
Section: Introductionmentioning
confidence: 99%
“…45-47 One of the most studied composites is Au/TiO2 material, which can be obtained by deposition-precipitation, colloidal synthesis or photodeposition of Au. [48][49][50][51][52] Recently, the reduction of CO2 to formate has been studied using Au and Pt loaded MOFs. 53 Herein, the goal of this study is to combine the GNPmodification of TiO2 with the possible advantages of using a Tibased MOF as sacrificial precursor for the TiO2 component while also acting as support matrix for the dispersion and stabilization of small GNPs.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, Pt@MOFs assemblies, prepared by photocatalytic deposition of Pt nanoparticles into the cavities of two phosphorescent UiO MOFs built from two Ir-phosphor-derived dicarboxylated ligands, were found to be effective photocatalysts for hydrogen generation. 23 In contrast, the nodes of MOFs possess the unique atomic coordination, 24,25 which holds a great potential for promoting unusual redox chemical reaction. On the other hand, the single site porous materials, in which foreigner metal ions were introduced in the skeleton of porous materials as a mediator have been applied for many photocatalytic application.…”
Section: Introductionmentioning
confidence: 99%
“…-oxide containing catalyst have also attracted much attention due to their visible light sensitivity and fascinating catalytic activities [9][10][11][12]. Our group has also demonstrated that transition metal oxides containing silica-based materials, which were called single-site photocatalyts, can be used not only to promote the photocatalytic reactions but also to form nanosized metals and alloys [1,13,14]. The preparation of binary oxide containing mesoporous silica was also successfully attained by photo-assisted deposition (PAD) technique, which shows the high selectivity in the partial oxidation of propylene into propylene oxide [13,15].…”
Section: Introductionmentioning
confidence: 99%